Proyecto de inversión para la creación de una Empresa dedicada a la Producción y Comercialización de embutidos a base de carne tierna de res con proceso de maduración para la Provincia de Zamora Chinchipe - Cabrera Piedra, Isaac Benito (2016)
The present thesis topic was developed with the objective of determining the feasibility of the investment project for the creation of a company dedicated to the production and marketing of sausage-based tender beef with maturing to the Zamora-Chinchipe province. The document details the factors and mechanisms necessary for the implementation of a sausage company, this proposal is intended to the industrialization of beef for its high content of nutrients. For the development of the research used a sample of 394 families in the province of Zamora-Chinchipe. The paper includes a comprehensive analysis at each stage of the proposed project. As the first point is detailed market research, which enabled to meet the tastes and preferences of the population. As well as also, knowing the current existing offer, key factors that allowed to determine the situation which we face and devise marketing strategies to be competitive and achieve a good market share. Determined that the 81.98% of households consume meats, families willing to buy the product are 19.397, all of this based on a study in nine cantons in the province. Then, in the technical study is detailed step by step production process to follow from the purchase of raw material to the finished consumer product distribution. In addition, the location is set optimal plant processing, prior analysis of some factors influencing the same and sets that Zamora is located in the canton (Parish Cumbaratza, 1.1 km from the airstrip, Yantzaza via), plant size is directly related to the production capacity of the machinery used and operators to hire. Daily 5 intends to produce 1650 pounds of sausage from three different classes and work 252 days a year, more 408 hours further, giving us a total annual production of 499.950 pounds of sausage from three varieties. Also describes the structural and functional organization chart establishing hierarchical dependencies, so a good administrative organization, also listed all the requirements needed to operate the plant of sausages, which require different supervisory bodies. Finally, developed the financial study which details, the cost of raw materials required, costs and expenses, all these product all the production process. The total investment required is $540.803, 94, of which 63, 02% will constitute the contribution of the partners and the 36.98% will be funded by the CFN to 9.45% annual interest. When applying the financial indicators is obtained as a result a net present value (range) of $1.153.472, 32, the benefit cost ratio (RB/C) of 1.31, the internal rate of return (IRR) equal to 73.97%, the period of recovery of the Capital (PRC) 1 year, 6 months and 7 days, the sensitivity in the increase in costs of 36.167% and 223.946% revenue decrease sensitivity. These results show that the project is feasible.